Pseudoescópula em Ischnothele annulata (Araneae, Mygalomorphae): avaliando estrutura e funcionalidade na comunicação sexual - Jurgilas, Juliana Paneczko [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Spiders are generally solitary, aggressive, potential cannibal predators, and have poor visual acuity. These features may have favored a strong selection for long-distance communication, such as chemical and/or vibratory signaling. The pheromone usage is an example of signal used during intersexual communication and have been chemically identified in eleven araneomorph species. To the emission of the pheromones, females can use their cuticle or web, and for the perception of these substances, araneomorph males use chemosensory setae located in the dorsal side of the pedipalps. In mygalomorphs, it was reported the presence of a chemosensory setae in an Idiops pylorus male, identified by Scanning Electron Microscopy micrographies. Besides that, recently it was reported a tarsal setae exclusive of mygalomorph males, that have been considered a chemosensory setae because of it’s similarity with the one’s found in Idiops pylorus, and even with the ones found in araneomorphs, despite the contrast in disposition of the setae between the infraorders. They can be arranged densely on tarsus, similar to those setae found in the scopula (and in this case, named pseudoscopula), or be sparsely distributed on ventral tarsus among other setae types. These male setae also differ from other chemosensory ones that are widespread in both males and females of mygalomorph spiders In the present study, the pseudoscopula of a mygalomorph representative, Ischnothele annulata, was investigated through bioassays and transmission electron microscopy. The results indicate that the males identify the conspecific females by chemical signals present in the female silk (contact recognition), and that they do not use long range (volatile) signals to find a mate. The pseudoscopula setae seems to be accountable for the recognition, since the obstruction of the setae prevent males to react to the silk, failing to perform typical courtship when in contact with female’s web. The transmission electronic microscopy analysis of the pseudoscopula seems to indicate a patter similar to those found in chemosensory setae of other group of spiders.

As aranhas geralmente são criaturas solitárias, de pouca acuidade visual, agressivas e potenciais predadoras canibais, características que podem ter selecionado formas de comunicação à longa distância, como sinais químicos e/ou vibratórios. Os feromônios são um exemplo de sinal utilizado durante a comunicação intersexual, já tendo sido caracterizado quimicamente para onze espécies de araneomorfas. A emissão dessas substâncias é feita pelas fêmeas por meio da seda ou pela cutícula. Para sua recepção, machos de araneomorfas utilizam cerdas quimiossensoriais presentes no dorso dos palpos. Para migalomorfas, foi reportada a presença de cerdas quimiossensorias em um macho de Idiops pylorus a partir de análises de Microscopia Eletrônica de Transmissão. Além disso, recentemente foi reportada a presença de uma cerda tarsal exclusiva de machos de Mygalomorphae, que por sua similaridade com as encontradas em I. pylorus, e até mesmo com as cerdas quimiossensoriais encontradas em araneomorfas, também foi considerada quimiossensorial, apesar da diferença de disposição entre as duas infraordens. Elas podem estar arranjadas de forma densa (sendo chamadas pseudoescópula), ou estarem esparsamente distribuídas juntamente com outros tipos de cerda. Estas cerdas também diferem de outras sensoriais que são amplamente encontradas em machos e fêmeas de migalomorfas. No presente estudo, as cerdas da pseudoescópula de um representante de Mygalomorphae, Ischnothele annulata, foram investigadas por meio de bioensaios e microscopia eletrônica de transmissão. Os resultados indicam que os machos da espécie em questão se utilizam de sinais químicos presentes na teia das fêmeas (contato) para o reconhecimento intraespecífico, além de não utilizarem sinais de origem volátil (longo alcance) para encontrar as parceiras. As cerdas da pseudoescópula parecem ser as responsáveis pelo reconhecimento, uma vez que a obstrução dessas cerdas impede que os machos realizem movimentos de corte típicos da espécie quando entram em contato com a teia das fêmeas. As análises da cerda a partir de técnicas de Microscopia Eletrônica de Transmissão também parecem indicar um padrão similar ao encontrado em cerdas quimiossensoriais de outro grupo de aranhas.
Pseudoscopula in Ischonothele annulata (Araneae, Mygalomorphae): evaluating structure and functionality in sexual communication
Keywords: Feromonas; Animais comportamento; Comunicação na biologia; Zoologia; Comunicação química; Ultraestrutura; Feromônio; Chemical communication; Ultrastructure; Pheromone